Fenomena Tingginya Permohonan Isbat Nikah di Pengadilan Agama Sibuhuan: Analisis Faktor Sosial, Kultural, dan Yuridis - Nur Fitryani Siregar; Azhar Majid Hasibuan; Kalijunjung Hasibuan (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
This study aims to identify the issues surrounding marriage validation under Islamic law and the factors influencing marriage validation applications at the Sibuhuan Religious Court. This study was conducted as a field research study using descriptive qualitative methods. The results indicate that the issues surrounding marriage validation under Islamic law include marriages occurring within the context of divorce settlements, lost marriage certificates, doubts about the validity of one of the marriage requirements, and neglect by the husband and wife regarding the administrative procedures of a marriage. Factors influencing marriage validation applications at the Sibuhuan Religious Court include: first, local customs still believed by the applicant; second, the applicant's knowledge of legal issues and the low level of public legal awareness; third, the applicant has registered the marriage through the marriage registrar/Village Registrar's Assistant, but the registrar has not forwarded it to the Religious Affairs Office, thus preventing them from obtaining a marriage certificate; fourth, age, as the applicant was underage at the time of the marriage, resulting in the rejection of the marriage application by the local Religious Affairs Office; and fifth, natural factors.